2021
DOI: 10.1371/journal.pone.0251551
|View full text |Cite
|
Sign up to set email alerts
|

Happy just because. A cross-cultural study on subjective wellbeing in three Indigenous societies

Abstract: While cross-cultural research on subjective well-being and its multiple drivers is growing, the study of happiness among Indigenous peoples continues to be under-represented in the literature. In this work, we measure life satisfaction through open-ended questionnaires to explore levels and drivers of subjective well-being among 474 adults in three Indigenous societies across the tropics: the Tsimane’ in Bolivian lowland Amazonia, the Baka in southeastern Cameroon, and the Punan in Indonesian Borneo. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…This is at odds with the consensus view given in ref. 29 , but is consistent with previous cross-cultural studies of subjective well-being suggesting that most people are fairly happy by default ( 23 , 56 ). It also underscores the dominant role that nonmaterial factors, such as social support and trust, could play in raising the future happiness of peoples across the world ( 57 ).…”
supporting
confidence: 90%
“…This is at odds with the consensus view given in ref. 29 , but is consistent with previous cross-cultural studies of subjective well-being suggesting that most people are fairly happy by default ( 23 , 56 ). It also underscores the dominant role that nonmaterial factors, such as social support and trust, could play in raising the future happiness of peoples across the world ( 57 ).…”
supporting
confidence: 90%
“…For example, in an European-American cultural context, the definition of well-being relies heavily on high arousal positive emotions and individual achievement, whereas in an East Asian cultural context, well-being is defined in terms of both positive and negative emotions and close interpersonal relationships (Uchida & Ogihara, 2012 ). Understanding of well-being in many African countries is rooted in relational and material, rather than psychological, aspects of life (e.g., White & Jha, 2018 ), whereas health has a key role in life satisfaction judgments in many Indigenous societies with limited access to health care services (Reyes-García et al, 2021 ). Research on lay conceptualizations of well-being and the good life across different countries and continents clearly show that these concepts are complex, and encompass a wide variety of ideas and beliefs which might lead to different understanding of life satisfaction across cultures, and consequently to different functioning of SWLS items among samples from different cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Some aspects of happiness appear to be similar in diverse cultural settings, even in childhood ( Song et al, 2020 ), while others have been found to vary across cultures from the earliest stages of the life cycle ( Rajhans et al, 2016 ; Liu et al, 2021 ). These variations are due to differences in parenting practices, and in the beliefs and rules governing both personal and social conduct and the evaluation of life events ( Jordan and Graham, 2012 ; Simsek and Demir, 2014 ; Rudan et al, 2016 ; Reyes-Garcia et al, 2021 ; von Suchodoletz and Hepach, 2021 ; Wang, 2022 ). All of these are fundamentally “rooted in culture and tradition” ( Daniels, 2019 ).…”
Section: Introductionmentioning
confidence: 99%